1983
DOI: 10.1073/pnas.80.2.412
|View full text |Cite
|
Sign up to set email alerts
|

P85 gag-mos encoded by ts110 Moloney murine sarcoma virus has an associated protein kinase activity

Abstract: A protein identified as P859'9-°was shown to be phosphorylated when immunoprecipitates from tsllO Moloney murine sarcoma virus transformed nonproducer cells (clone 6m2) were incubated with [y-32P]ATP. The in vitro-labeled 85,000-dalton phosphoprotein comigrated on NaDodSO4/polyacrylamide gels with authentic phosphorylated P859'9-°. Immunoprecipitates obtained with antisera prepared against Rauscher murine leukemia virus core protein p30 were active in the immune complex kinase assay but anti-murine leukemia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
1

Year Published

1985
1985
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 31 publications
(29 reference statements)
2
44
1
Order By: Relevance
“…abl kinase activity was not inhibited when protein A-Sepharose was used instead of S. aureus. The new reaction conditions described in this paper should also be useful for studying other kinases, particularly those forms of the v-mos protein which have homology to the kinase family but no detectable kinase activity (33), in contrast to gag-mos strains with serine kinase activity (24).…”
Section: P145c-ah" Isolated From Ph'-positive K562 Cells (Data Notmentioning
confidence: 99%
“…abl kinase activity was not inhibited when protein A-Sepharose was used instead of S. aureus. The new reaction conditions described in this paper should also be useful for studying other kinases, particularly those forms of the v-mos protein which have homology to the kinase family but no detectable kinase activity (33), in contrast to gag-mos strains with serine kinase activity (24).…”
Section: P145c-ah" Isolated From Ph'-positive K562 Cells (Data Notmentioning
confidence: 99%
“…Nevertheless, we cannot completely rule out the possibility that the c-abl P210 tyrosine kinase catalytic domain actually has dual specificity or that the serine phosphorylation is a result of the additional, unidentified amino-terminal sequences in c-abl P210. It has been reported that the P85gag-mos protein of the tsllO Moloney murine sarcoma virus has an associated serine and threonine kinase activity in vitro (13). Normal murine and human c-abl proteins are phosphorylated on serine in vivo.…”
mentioning
confidence: 99%
“…Since the function of the v-mos gene product has yet to be determined, neither its original role as a c-mos gene product nor its method of transformation when expressed by a retrovirus is known (12,27,35). Our work delineates the N-and C-terminal regions of the mos gene requisite for biological activity and consequently the sequences which are indispensable for an active v-mos gene product.…”
Section: Methodsmentioning
confidence: 94%
“…The v-mos gene product is one of several oncogenic proteins which show homology to the bovine cAMPdependent protein kinase but possess no specific tyrosine kinase activity (3,27). There are several specific regions within the v-rnos gene product which show conservation of residues with the protein kinase (Fig.…”
Section: Methodsmentioning
confidence: 99%